Structural basis of l-tryptophan-dependent inhibition of release factor 2 by the TnaC arrest peptide. Issue 16 (17th August 2021) - Su, Ting; Kudva, Renuka; Becker, Thomas; Buschauer, Robert; Komar, Tobias; Berninghausen, Otto; von Heijne, Gunnar; Cheng, Jingdong; Beckmann, Roland
Abstract: In  Escherichia coli, elevated levels of free l -tryptophan (l -Trp) promote translational arrest of the TnaC peptide by inhibiting its termination. However, the mechanism by which translation-termination by the UGA-specific decoding release factor 2 (RF2) is inhibited at the UGA stop codon of stalled TnaC-ribosome-nascent chain complexes has so far been ambiguous. This study presents cryo-EM structures for ribosomes stalled by TnaC in the absence and presence of RF2 at average resolutions of 2.9 and 3.5 Å, respectively. Stalled TnaC assumes a distinct conformation composed of two small α-helices that act together with residues in the peptide exit tunnel (PET) to coordinate a single L-Trp molecule. In addition, while the peptidyl-transferase center (PTC) is locked in a conformation that allows RF2 to adopt its canonical position in the ribosome, it prevents the conserved and catalytically essential GGQ motif of RF2 from adopting its active conformation in the PTC. This explains how translation of the TnaC peptide effectively allows the ribosome to function as a L-Trp-specific small-molecule sensor that regulates the tnaCAB operon.